Designated Market Makers: Competition and Incentives - Mario Bellia; Loriana Pelizzon; Marti G. Subrahmanyam; Darya Yuferova (Leibniz Institute for Financial Research SAFE, 2020)
Do competition and incentives offered to designated market makers (DMMs) improve market liquidity? Using data from the NYSE Euronext Paris, we show that an exogenous increase in competition among DMMs leads to a significant decrease in quoted and effective spreads, mainly through a reduction in the realized spread. In contrast, changes in incentives, through small changes in rebates and requirements for DMMs, do not have any tangible effect on market liquidity. Our analysis shows that incentivizing DMMs might not necessary lead to an improvement of market liquidity unless exchanges induce greater competition among DMMs.
Keywords: G12; G14; 330; Designated Market Makers; DMMs; Liquidity Provision